Reliability Analysis on Random Meshing Efficiency of Helical Gear based on Monte Carlo Method - Mingyong Hu; Yunbo Hu; Jinku Li; Wei Liu (Jixie chuandong, 2021)
Based on the Monte Carlo method，the reliability model of random meshing efficiency of helical gears is established. Five parameters that have a greater impact on the meshing efficiency are selected as random parameters. Through the normal distribution sampling of the random parameters，the reliability effects of each random parameter on the meshing efficiency are obtained. The results show that the normal modulus and the helix angle have the smallest effect on the meshing efficiency of helical gear，which are similar，the second is the tooth width，the third is the normal pressure angle，the most influential is the addendum height coefficient h. Therefore，in the design and manufacture of helical gear transmission systems considering meshing efficiency，the contact strength and bending strength of helical gears can be improved by optimizing the normal modulus ，helix angle β and tooth width to reduce the impact on meshing efficiency.